Radiomics & Radiology: A Critical Step towards Integrated Healthcare - Mayur Pankhania; Mehta, Aditya (Asian Journal of Medical Radiological Research, 2020)
Radiomics have shown great promise for integrated healthcare. Radiomics is defined as high-performance retrieval of significant volumes of characteristics from images and conversion of images to higher-dimensional data and subsequently mining for improved support for therapeutic judgements. It has its roots within Computer-Aided Detection (CAD)or Computer-Aided Diagnosis (CADx); it is unique in many aspects. It does not just detect and diagnose but also ventures into therapeutic, prediction, projection and modelling that can be used to generalize and reproduced. It has great potential in creating a paradigm shift in the way healthcare is delivered and perceived. We will review and outline the stage of radiomics& its SWOT analysis, exclusively addressing application in medical imaging and spotlighting the technical issues.